The French Right-Wing Paradox – Maintaining the cordon sanitaire - Emilien Houard-Vial (Partecipazione e Conflitto, 2022)
In this article, we explain why the French mainstream right-wing party, today Les Républicains, has maintained until now a cordon sanitaire between itself and its far-right counterpart, the Rassemblement National. We examine the usual hypotheses identified by the literature on coalitions between mainstream and far-right parties, and confirm that they are not able to explain the French case. We argue that this paradox can be solved by re-evaluating some core ideological disagreements, as well as the importance of competence and credibility in the party image of the mainstream right, which we identify – discussing Panebianco's genetic model – as a result of its historical role of governmental, established party.